Comparative Study of Fixed-Wing and Rotary-Wing Aircraft: A Systematic Literature-Based Analysis of Flight Efficiency, Maneuverability, and Operational Function - Hadi Prayitno; Gunawan Sakti; Ahmad Bahrawi; Dani Chandra Yudho Pranoto; Moch Rifai (Indonesia Civil Pilot Academy Banyuwagi, 2026)
This study compares fixed-wing and rotary-wing aircraft in terms of flight efficiency, maneuverability, and operational function by addressing the lack of an integrated framework for mission-based aircraft comparison. A systematic literature-based comparative analysis was conducted using aerodynamics textbooks, aviation handbooks, technical references, regulatory documents, and recent scholarly articles. The analysis was structured around three parameters: flight efficiency, including energy consumption, cruising speed, and range; maneuverability, including takeoff and landing capability, hovering, and movement flexibility; and operational function, including mission suitability and operating environment. The findings show that fixed-wing aircraft provide higher cruise efficiency, greater range, and better payload effectiveness because lift is generated through forward motion over fixed airfoils. In contrast, rotary-wing aircraft offer superior maneuverability, vertical takeoff and landing, and hovering capability, making them more suitable for confined-area, emergency, and point-access missions. The novelty of this study lies in its structured analytical matrix, which clarifies the trade-off between cruise efficiency and spatial flexibility. The study concludes that neither aircraft type is universally superior; effectiveness depends on the alignment between aerodynamic characteristics, operational constraints, and mission requirements.